قانون اللباس الموحد في إيران عام 1928 م والموقف الشعبي منه: دراسة وثائقية - عبدالعلاق، أحمد شاكر (جامعة الكوفة - كلية التربية للبنات, 2019)
The phenomenon of change of clothes in Iran during the reign of Reza Shah Pahlavi of the most prominent historical stations witnessed by Iran on the social level, where Arad, Shah Reza of such a move Reload Iran and walk by on the way to the West with respect to ideas and visions and way of life in terms of housing, employment and dress. To achieve this, Shah Reza began himself, has applied the new law, which was issued in 1928, the people of his home, trying to pave the way for the general public to apply. We follow Reza Pahlavi various methods in order to achieve uniform law, including the Women's Police and the establishment of seminars, conferences and cultural gatherings backed by the government establishment, to educate the uniform law and to facilitate the abandonment of traditional dress, and to require state employees to wear western dress code during and after the conduct of their work process. I've been to this law, significant economic and social effects on all levels, has been affected Iran economies negatively because of the application of the law for non-domestic market is unable to meet the needs of the people, which Iran was forced to increase foreign exports, which reflected negatively on all the traditional industrial sectors in the country, many of those plants and factories were forced to close their doors and lay off workers due to their inability to keep up with foreign goods imported. Reza Shah did not pass those measures without opposition Iranian street, if the task of leading the masses of the religious establishment opposition to the law came after he openly declared that the paragraphs of the law represented a flagrant violation of the teachings of Islamic law. Despite the fact that some of its paragraphs untouched dress clergy, is that the objection was focused on ways to apply it and compel people to abandon traditional dress and wear Arta West."
Keywords: قانون اللباس الموحد -- المجتمع الإيرانى